Historical causes of Romanian socialism institutionalization - GHIORGHIŢĂ, Eugen (Annals of Spiru Haret University. Economic Series, 2012)
The natural classification of socialism in the evolution of the history of humanity is one more difficulty for many thinkers. Surprisingly enough, many intelligent people try to deny the sense of history by challenging historical reality. In other words, though it existed, it would have been much better for socialism not to have existed in the history of humanity. The dereliction of socialist ideology after 1989, the cancellation or ridicule of the principles and ideals expressed in the cant of the boring and demonetized slogans prove the fragility of the much-invoked damage of the so-called communist politics as an essence of the system. It was not the ideology, or the code of the communists’ ethics or the supremacy of socialist property that made up the sense and essence of socialism as applied after 1948. The ‘objective’ of applied socialism was the forced, accelerated development of the economies of the central and south-eastern European countries, based on the experience of USSR for the compatibility of the structure of the consumption demand of their inhabitants with the supply of the industrialized countries in a historical interval as soon as possible. God knows whether the effects of extending capitalism in these countries instead of socialism would have been the same or maybe even better until 1989! The fact is that socialism was imposed from the outside, without following in any way whatsoever the Marxist schedule of proletarian revolution determined by the enhancement of internal class contradictions. The study of the League of Nations in 1945 reveals the programmatic character or, if not, at least the prophetic character of the advanced analyses and forecasts based on the developments of the 1870-1938 period. during the interwar period, the gaps between the manufactured products exporting countries and the raw materials supplying countries widened; the diminution of the purchasing power in the countries exporting the basic commodities put more acutely in danger the sales of the countries manufacturing processed industrial goods; the economic gaps between the West and the East, i.e. the North and the South, could be reduced only by the fast industrialization of the countries exporting raw materials; the role of the external capital in the development of national economies was proved to be the least controversial; the internal, national accumulation was decisive; the free initiative, individualism and pseudo-market economy had proven their limits, as they had been ineffective for an accelerated development of the countries during early industrialization; the study of the League of Nations highlights the need of the constant intervention of the state in economy by means of central planning. Though socialism was not expressly recommended as the best solution for the forced economic growth and development of the raw materials supplying countries, the study of the League of Nations in 1945 argues and supports measures and convergent ways of action to a very similar socio-economic system.